Pea production and commercialization in the department of Nariño-Colombia - Torres-Martínez, Francisco Javier (2020)
Introduction. Traditional agricultural production systems prevail in the southern region of Nariño, however, the area harvested from transitory potato, corn and beans crops has been decreased. To address this problem, pea planting has been strengthened, which is marketed in local and regional markets. The department of Nariño is the first pea producer in Colombia, and in 2018, 9425 ha were reported, with an average yield of 1.19 t ha-1. The farmers in the study area are traditional and show technical limitations of production and commercialization. Objective. The objective of the investigation was to analyze the production and commercialization of peas in the department of Nariño. Materials and methods. The research was descriptive and allowed to establish costs, production volumes, planting times, product characteristics, prices, and marketing during 2012. The target population included producers, municipal intermediaries, wholesalers and retailers, and association leaders located in the pea-producing municipalities. Results. The Andean variety was the most sown, the post-harvest losses were 52 %, the prices vary due to the seasonality of production, and the greater volume of production was channeled through intermediaries. Conclusions. The production and commercialization of peas in Nariño presents difficulties that requiere sowing planning to balance production volumes, access development credit, train and organize farmers, and foster strategic alliances to guarantee conditions in the value chain. Keywords: productivity, competitiveness, value generation, production flow.